Finite-state wake inflow models for rotorcraft flight dynamics in ground effect - Cardito, F.; Serafini, J.; Pasquali, C.; Bernardini, G.; Gennaretti, M.; Celi, R. (My University, 2017)
Rotor wake inflow plays a crucial role in rotorcraft aeromechanics and, on the other side, it is strictly dependent on the operating condition. The presence of the ground below the rotor disc affects rotor aerodynamics, especially through the modification of wake inflow with respect to free-air operative condition. Here, the effect of ground on wake inflow and aeromechanic response and stability is investigated. Linear, time-invariant dynamic inflow models, extracted from highfidelity aerodynamic simulations and suited for aeromechanic analysis, are presented. One provides the wake inflow as a function of rotor kinematic variables, while the second one gives the wake inflow as forced by rotor loads. In both cases, first the involved transfer functions are identified through time-marching aerodynamic simulations, and then a rationalmatrix formula is applied for their finite-state approximation. In-ground-effect and out-of-ground-effect state-space inflow models are applied for helicopter response and stability analyses, and the corresponding results are compared to discuss the influence of ground on aeromechanics.